Current status of the problem of anxiety disorders and factors of the pathomorphose of anxiety syndrome - Kurylo, Vitaliy (Journal of Education, Health and Sport, 2025)
Objective: To synthesize current scientific literature on the epidemiology, clinico-psychological correlates, and clinical pathomorphosis of anxiety disorders, aiming to generalize key features of the anxiety syndrome. Materials and Methods: A comprehensive analysis of contemporary scientific publications, including systematic reviews and meta-analyses, was conducted to identify current trends in the understanding and management of anxiety. Results: The review confirms that anxiety disorders are a highly prevalent, heterogeneous, and exceptionally comorbid pathology, frequently overlapping with mood, pain, and substance use disorders. Pathomorphosis of the syndrome was significant, frequently manifesting as “masked” anxiety. This involves a predominance of somatic or vegetative symptoms (e.g., chronic pain, functional dysfunction) presented in primary care, rather than classic psychiatric complaints. This clinical presentation is strongly linked to psychological constructs of alexithymia and poor insight, which impede emotional awareness and verbalization. These deficits impede diagnosis, result in excessive medical investigations, and reduce CBT efficacy due to its reliance on cognitive-emotional processing. Conclusions: Anxiety disorders are a prevalent, heterogeneous, and highly comorbid pathology. Major challenges include the somatization of symptoms and patients' low insight, which necessitates a transdiagnostic approach and interventions aimed at improving self-awareness.